Polyamide resin composition, method for preparing same, and molded article comprising same
By combining polyamide resin, glass fiber, and ether compounds with specific OH values, the problem of insufficient heat resistance of polyamide resin in high-temperature environments is solved, achieving excellent tensile strength and flexural modulus, making it suitable for automotive or electrical and electronic products in high-temperature environments.
Patent Information
- Application Number
- CN202480006428.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-05-02
- Filing Date
- 2024-12-11
- Publication Date
- 2026-01-06
AI Technical Summary
Existing polyamide resins have insufficient heat resistance in high-temperature environments, leading to whitening and making them unsuitable for use in automotive or electrical and electronic components that require temperatures above 200°C.
A polyamide resin composition is prepared by kneading and extrusion using a combination of polyamide resin, glass fiber, and ether compounds with specific OH values, including ether compounds with OH values of 35 mg KOH/g to 40 mg KOH/g and 1190 mg KOH/g to 1320 mg KOH/g, with the addition of heat stabilizers, light stabilizers, and lubricants.
It improves the tensile strength and flexural modulus of polyamide resin, enhances heat resistance, avoids whitening, and is suitable for environments above 150°C, making it suitable for automobiles or electrical and electronic products.
Smart Images

Figure BDA0005477386840000171 
Figure BDA0005477386840000181
Abstract
Description
Technical Field
[0001] [Cross-references to related applications]
[0002] This application claims priority to Korean Patent Application No. 10-2024-0058654, filed with the Korean Intellectual Property Office on May 2, 2024, the disclosure of which is incorporated herein by reference.
[0003] This invention relates to a polyamide resin composition, a method for preparing the polyamide resin composition, and a molding article comprising the polyamide resin composition. More specifically, this invention relates to a polyamide resin composition having excellent tensile strength and flexural modulus, which minimizes the thermal effects of exposure to the external environment due to its excellent heat resistance, and is suitable for automotive or electrical / electronic products used in environments with operating temperatures exceeding 150°C or automotive or electrical / electronic products requiring heat resistance above 200°C; a method for preparing the polyamide resin composition; and a molding article comprising the polyamide resin composition. Background Technology
[0004] Recently, many studies have been conducted to improve the fuel efficiency of automobiles by using resins to manufacture automotive parts. Polyamide resins, which have excellent heat resistance and solvent resistance, are widely used as materials for automotive parts.
[0005] However, due to its insufficient heat resistance, polyamide resins are difficult to apply to automotive parts or electrical and electronic components that require heat resistance exceeding 200°C.
[0006] Meanwhile, representative heat stabilizers that provide heat resistance to polyamide resins include polyols such as pentaerythritol, dipentaerythritol, and tripentaerythritol.
[0007] However, while these components provide high thermal stability, they also have the drawback of causing whitening, which results in the product surface turning white due to migration under high temperature and high humidity conditions.
[0008] Therefore, there is an urgent need to develop a polyamide resin composition that has excellent tensile strength, flexural modulus and heat resistance, does not cause whitening, and can be used in automotive parts or electrical and electronic components.
[0009] [Related Technical Documents]
[0010] [Patent Literature]
[0011] Japanese Patent Application Publication 2014-148560 Summary of the Invention
[0012] Technical issues
[0013] Therefore, the present invention has been made in view of the above-mentioned problems, and one object of the present invention is to provide: a polyamide resin composition having excellent tensile strength and flexural modulus, being able to minimize the thermal effects caused by exposure to the external environment due to its excellent heat resistance, and being a suitable material as a substitute for metal parts of automobiles or electrical and electronic devices used in high-temperature environments; a method for preparing the polyamide resin composition; and a molding article comprising the polyamide resin composition.
[0014] The above and other objectives can be achieved by the invention described below.
[0015] Technical solution
[0016] I) According to one aspect of the present invention, a polyamide resin composition is provided, comprising: polyamide resin (A), glass fiber (B) and ether compound (C), wherein the ether compound (C) comprises ether compound (C-1) with an OH value of 35 mg KOH / g to 40 mg KOH / g and ether compound (C-2) with an OH value of 1190 mg KOH / g to 1320 mg KOH / g.
[0017] II) According to another aspect of the present invention, a polyamide resin composition is provided, comprising: 39% to 95% by weight of polyamide resin (A), 4.4% to 40% by weight of glass fiber (B), 0.5% to 10% by weight of an ether compound with an OH value of 35 mg KOH / g to 40 mg KOH / g (C-1), 0.1% to 10% by weight of an ether compound with an OH value of 1190 mg KOH / g to 1320 mg KOH / g (C-2), and less than 5% by weight of additives (D).
[0018] III) According to I) to II), the ether compound (C-1) may have a number-average molecular weight of less than 20,000 g / mol.
[0019] IV) According to I) to III), the ether compound (C-2) may have a number-average molecular weight of less than 2,000 g / mol.
[0020] V) According to I) to IV), the ether compound (C-1) and the ether compound (C-2) may be contained in a weight ratio of 1:0.5 to 1:5 (C-1:C-2).
[0021] VI) According to I) to V), the glass fiber may comprise: 52% to 56% by weight of silicon dioxide; 12% to 16% by weight of aluminum oxide; 21% to 25% by weight of calcium oxide and magnesium oxide (magnesium oxide: less than 1.5% by weight); less than 1% by weight of titanium dioxide; 5% to 8% by weight of boron oxide; and less than 2.0% by weight of the remainder comprising sodium oxide, potassium oxide and iron oxide.
[0022] VII) According to I) to VI), the additive may include one or more selected from heat stabilizers, light stabilizers, lubricants and antioxidants.
[0023] VIII) According to I) to VII), the polyamide resin composition may have a tensile strength of more than 170 MPa as measured according to ISO 527 at a marking distance of 50 mm, a test speed of 5.0 mm / min and a temperature of 23 °C.
[0024] IX) According to I) to VIII), the polyamide resin composition may have a flexural modulus of more than 8,000 MPa as measured according to ISO 178 at a span of 64 mm and a test speed of 2.0 mm / min.
[0025] X) According to another aspect of the present invention, a method for preparing a polyamide resin composition is provided, the method comprising kneading and extruding a polyamide resin (A), glass fiber (B) and an ether compound (C), wherein the ether compound (C) comprises an ether compound (C-1) with an OH value of 35 mg KOH / g to 40 mg KOH / g and an ether compound (C-2) with an OH value of 1190 mg KOH / g to 1320 mg KOH / g.
[0026] XI) According to another aspect of the present invention, a method for preparing a polyamide resin composition is provided, the method comprising kneading and extruding 39% to 89.4% by weight of polyamide resin (A), 4.4% to 40% by weight of glass fiber (B), 0.5% to 10% by weight of an ether compound with an OH value of 35 mg KOH / g to 40 mg KOH / g (C-1), 0.1% to 10% by weight of an ether compound with an OH value of 1190 mg KOH / g to 1320 mg KOH / g (C-2), and 0 to 5% by weight of additives.
[0027] According to X) to XI), the extrusion conditions can be temperature conditions of 280°C to 310°C.
[0028] XIII) According to another aspect of the present invention, a molding article comprising the above-described polyamide resin composition is provided.
[0029] According to XIII), the molded article may be an automotive part or an electrical and electronic part.
[0030] Beneficial effects
[0031] According to the present invention, the present invention has the following effects: providing a polyamide resin composition having excellent tensile strength and flexural modulus, which, due to its excellent heat resistance, can minimize the thermal effects caused by exposure to the external environment, and is suitable for automobiles or electrical / electronic products used in environments with operating temperatures exceeding 150°C or automobiles or electrical / electronic products requiring heat resistance above 200°C; a method for preparing the polyamide resin composition; and a molding article comprising the polyamide resin composition. Detailed Implementation
[0032] The polyamide resin composition of the present invention, the method for preparing the polyamide resin composition, and the molding article comprising the polyamide resin composition will be described in detail below.
[0033] The inventors have confirmed that when a polyamide resin composition is prepared by mixing polyamide resin, glass fiber, and an ether compound satisfying a specific OH value in a predetermined compositional ratio, molded articles comprising this polyamide resin composition exhibit excellent tensile strength, flexural modulus, and heat resistance, and are virtually unaffected by heat caused by exposure to the external environment. Based on these results, the inventors conducted further research to complete this invention.
[0034] The polyamide resin composition of the present invention comprises a polyamide resin, glass fiber, and two ether compounds with different OH values. In this case, tensile strength and flexural modulus can be excellent, and the effects of heat due to exposure to the external environment can be minimized due to excellent heat resistance. Therefore, the polyamide resin composition can be used in automotive or electrical / electronic products used in environments with operating temperatures exceeding 150°C, or in automotive or electrical / electronic products requiring heat resistance above 200°C.
[0035] As another example, the polyamide resin composition of the present invention comprises a polyamide resin (A), glass fiber (B), and an ether compound (C). The ether compound (C) includes ether compound (C-1) with an OH value of 35 mg KOH / g to 40 mg KOH / g and ether compound (C-2) with an OH value of 1190 mg KOH / g to 1320 mg KOH / g. In this case, tensile strength and flexural modulus can be excellent, and the effects of heat due to exposure to the external environment can be minimized due to excellent heat resistance. Therefore, the polyamide resin composition can be used in automotive or electrical / electronic products used in environments with operating temperatures exceeding 150°C, as well as automotive or electrical / electronic products requiring heat resistance above 200°C.
[0036] As another example, the polyamide resin composition of the present invention comprises 39% to 89.4% by weight of polyamide resin, 4.4% to 40% by weight of glass fiber (B), 0.5% to 10% by weight of an ether compound with an OH value of 35 mg KOH / g to 40 mg KOH / g (C-1), 0.1% to 10% by weight of an ether compound with an OH value of 1190 mg KOH / g to 1320 mg KOH / g (C-2), and less than 5% by weight of additives (D). In this case, the tensile strength and flexural modulus can be excellent, and the thermal effects caused by exposure to the external environment can be minimized due to excellent heat resistance. Therefore, the polyamide resin composition can be used in automotive or electrical / electronic products used in environments with operating temperatures exceeding 150°C, as well as automotive or electrical / electronic products requiring heat resistance above 200°C.
[0037] The components constituting the polyamide resin composition of the present invention are described in detail below.
[0038] (A) Polyamide resin
[0039] For example, the polyamides of the present invention may include those selected from polyamide 6, polyamide 66, polyamide 46, polyamide 11, polyamide 12, polyamide 610, polyamide 612, polyamide 6 / 66, polyamide 6 / 612, polyamide MXD6, polyamide 6 / MXD6, polyamide 66 / MXD6, polyamide 6T, polyamide 6I, polyamide 6 / 6T, polyamide 6 / 6I, polyamide 66 / 6T, polyamide 66 / 6I, polyamide 6 / 6T / 6I, etc. One or more of polyamide 66 / 6T / 6I, polyamide 9T, polyamide 9I, polyamide 6 / 9T, polyamide 6 / 9I, polyamide 66 / 9T, polyamide 6 / 12 / 9T, polyamide 66 / 12 / 9T, polyamide 6 / 12 / 9I, and polyamide 66 / 12 / 6I are preferred, and more preferably, homopolymers or copolymers selected from one or more of polyamide 6, polyamide 66, polyamide 46, polyamide 11, and polyamide 12 are preferred, with polyamide 66 being the most preferred. In this case, heat resistance, moldability, and chemical resistance can be excellent.
[0040] Based on a total of 100% by weight of polyamide resin composition, the polyamide may be included in an amount preferably more than 59% by weight, more preferably from 39% by weight to 89.4% by weight, and still more preferably from 59% by weight to 63% by weight. Within this range, mechanical properties such as tensile strength and impact strength, as well as heat resistance, can be excellent.
[0041] Within the scope defined by this invention, polyamides can be prepared by methods commonly used in the technical field to which this invention pertains, or commercially available products can be used, without particular limitation.
[0042] (B) Glass fiber
[0043] In this disclosure, glass fibers are included to improve the mechanical properties, heat resistance and dimensional stability of the polyamide resin composition.
[0044] When glass fiber is included in a polyamide resin composition, the mechanical properties of the molded articles formed from the resin composition, such as tensile strength, impact strength, elongation, and heat resistance, can be improved.
[0045] To ensure the required flowability of the resin composition in the field of molded parts using polyamide resin compositions, a specific glass material is introduced into the glass fiber. For example, when the glass fiber, described later, is used in the field of replacing metal materials in automotive system modules, sufficient heat resistance and mechanical properties of the base resin can be maintained, while sufficient processability and moldability can be ensured.
[0046] The glass fiber can be selected from at least one of a first glass fiber and a second glass fiber, wherein the first glass fiber has a tensile modulus of 83 GPa to 87 GPa as measured by ASTM D2343 for 17 μm-2400 tex rovings, and the second glass fiber has a tensile modulus of 88 GPa to 92 GPa. Using such high-strength glass fibers can reduce surface appearance defects caused by glass fiber protrusion or gas flow marks during injection molding. Furthermore, productization can be attempted by considering the performance deviations based on the orientation of the glass fibers in each component, which is advantageous in terms of flatness and deformation.
[0047] For example, the cross-section of glass fiber can be circular or non-circular, or it can be flat, including elliptical or irregular non-circular types.
[0048] In this disclosure, when the circular, elliptical, and irregular shapes are recognized as circular, elliptical, and irregular shapes in the technical field to which this invention pertains, there are no particular restrictions on the circular, elliptical, and irregular shapes of the cross-section.
[0049] In this disclosure, a circle refers to a cross-section with a size ratio of approximately 1 to 1 between the main cross-sectional axis and the secondary cross-sectional axis, but is not limited thereto.
[0050] In this disclosure, ellipse refers to a cross-section that is elliptical and the ratio of the main cross-sectional axis to the secondary cross-sectional axis is 2:6, 3:6, or 3.5:5.0, but is not limited thereto.
[0051] In this disclosure, amorphous shape refers to, but is not limited to, cases where the cross-section is not circular or elliptical.
[0052] In this disclosure, glass fibers can be used in combination with other inorganic fibers. For example, inorganic fibers may include one or more selected from carbon fibers, basalt fibers, and natural fibers such as kenaf or hemp.
[0053] The glass fiber of the present invention can be a glass fiber with a circular or non-circular cross-section, and its silica content is 52% by weight or more, or 52% by weight to 66% by weight. In this case, when product design and design changes are taken into account, it is possible to ensure high strength, lightweight and appearance quality that can replace existing metals.
[0054] For example, when the aspect ratio, expressed as the ratio of length (L) to diameter (D) (L / D), is measured, the polyamide resin composition of the present invention can provide high strength, high toughness, and improved elongation and surface appearance quality when the glass fibers have an aspect ratio of 1:1 to 1:4, specifically 1:1 to 1:3, and more specifically 1:1. When the aspect ratio is 1:3 to 1:4, and more specifically 1:4, products with high strength and high toughness and suitable flatness, deformation, and orientation can be provided.
[0055] In this disclosure, a scanning electron microscope (SEM) can be used to measure the diameter and length. Specifically, 20 inorganic fillers are selected using a scanning electron microscope, and the diameter and length of each inorganic filler are measured using a diameter-measuring icon bar. The average diameter and average length are then calculated.
[0056] For example, D can have an average diameter of 6 μm to 16 μm, preferably 7 μm to 11 μm, and more preferably 10 μm to 11 μm. Within this range, processing performance can be improved, and the tensile strength of molded articles manufactured by molding the polyamide resin composition of the present invention can be improved.
[0057] In this disclosure, the glass fiber may comprise 58% to 62% by weight of silica; 14% to 18% by weight of alumina; 17% to 24% by weight of calcium oxide and magnesium oxide (calcium oxide: more than 10% by weight, magnesium oxide: less than 10% by weight); 0.5% to 2% by weight of titanium dioxide; and less than 1.3% by weight of the remainder comprising sodium oxide, potassium oxide, and iron oxide. In this case, a polyamide resin composition with an excellent balance of physical properties in terms of processing performance, specific gravity, and mechanical properties can be ensured. Furthermore, using the polyamide resin composition, molded articles with high strength and high toughness that can replace metals can be provided.
[0058] The glass fiber may contain 52% to 56% by weight of silica; 12% to 16% by weight of alumina; 21% to 25% by weight of calcium oxide and magnesium oxide (magnesium oxide: less than 1.5% by weight); less than 1% by weight of titanium dioxide; 5% to 8% by weight of boron oxide; and less than 2.0% of the remainder, including sodium oxide, potassium oxide, and iron oxide. In this case, a polyamide resin composition with an excellent balance of physical properties in terms of processing performance, specific gravity, and mechanical properties can be ensured. Furthermore, using the polyamide resin composition, molded articles with high strength and high toughness can be provided as a substitute for metals.
[0059] The glass fiber can be a round glass fiber with a circular cross-section, containing a total calcium oxide and magnesium content of 17% to 24% by weight. In this case, a polyamide resin composition with an excellent balance of physical properties between processing performance, specific gravity, and mechanical properties can be ensured. Furthermore, using a polyamide resin composition, molded articles with high strength and high toughness can be provided as a substitute for metals.
[0060] The glass fiber can be a flat glass fiber with a non-circular cross-section, containing a total of 21% to 25% calcium oxide and magnesium. In this case, a polyamide resin composition with an excellent balance of physical properties, including processability, specific gravity, and mechanical properties, can be ensured. Furthermore, using polyamide resin compositions, molded articles with high strength and high toughness can be provided as a substitute for metals.
[0061] As a specific example, glass fiber can be represented by the general formula AaBbCcDd.
[0062] For the ultra-high strength grade, the characteristics for 0.5 ≤ c ≤ 5 are shown. For another general grade, the characteristics for 20 ≤ c ≤ 24, 2 ≤ d ≤ 5, and 22 ≤ c + d ≤ 29 in the general formula are shown, confirming that the composition is different.
[0063] Contrary to what is known in the art, the examples described below confirm that, in the polyamide resin compositions of the present invention, high-strength grades with circular cross-sections or non-circular (flat) high-strength flat grades are preferred over ultra-high-strength grades to improve tensile strength and injection moldability.
[0064] In this disclosure, during fiber manufacturing or post-processing, glass fibers can be treated with a glass fiber treatment agent (sizing composition), and the glass fiber treatment agent includes lubricants, coupling agents, surfactants, etc.
[0065] When manufacturing glass fibers, lubricants are primarily used to form good strands, while coupling agents play a role in achieving good adhesion between the glass fibers and the polyamide resin. When the types of polyamide resin and glass fibers are appropriately selected, excellent physical properties can be imparted to glass fiber-reinforced polyamide resin compositions.
[0066] Coupling agents can be applied directly to glass fibers or added to organic matrices. The appropriate concentration of the coupling agent can be selected to fully demonstrate its performance.
[0067] Examples of coupling agents include amine coupling agents, acrylic coupling agents, γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)γ-aminopropyltriethoxysilane, γ-methacryloyloxypropyltriethoxysilane, and γ-glycidoxypropyltrimethoxysilane.
[0068] As a specific example, the glass fiber may contain 58% to 62% by weight of silica; 14% to 18% by weight of alumina; 17% to 24% by weight of calcium oxide and magnesium oxide (calcium oxide: more than 10% by weight, magnesium oxide: less than 10% by weight); 0.5% to 2% by weight of titanium dioxide; and less than 1.3% by weight of the remainder, including sodium oxide, potassium oxide, and iron oxide. The glass fiber has a 1:1 aspect ratio (L / D) when measured as the ratio of length (L) to diameter (D). Circular high-strength glass fibers with diameters from 6 μm to 16 μm can be used.
[0069] As a specific example, the glass fiber may contain 52% to 56% by weight of silica; 12% to 16% by weight of alumina; 21% to 25% by weight of calcium oxide and magnesium oxide (magnesium oxide: less than 1.5% by weight); less than 1% by weight of titanium dioxide; 5% to 8% by weight of boron oxide; and less than 2.0% by weight of the remainder, including sodium oxide, potassium oxide, and iron oxide. When measured as the ratio of length (L) to diameter (D), the glass fiber has an aspect ratio (L / D) greater than 1:1 and less than 1:4. Non-circular, high-strength, flat glass fibers with diameters from 6 μm to 16 μm can be used.
[0070] Based on a total of 100% by weight of polyamide resin composition, glass fiber may be included in an amount preferably 30% by weight or more, more preferably 4.4% by weight to 40% by weight, and still more preferably 33% by weight to 38% by weight. Within this range, when product design and design changes are taken into account, high strength and appearance quality that can replace existing metals can be ensured.
[0071] Within the scope defined by this invention, glass fibers can be prepared by methods commonly used in the technical field to which this invention pertains, or commercially available products can be used, without particular limitation.
[0072] (C) Ether compounds
[0073] To prevent whitening and to achieve heat resistance at temperatures above 200°C, i.e. to provide thermal stability, the ether compound of the present invention is added to the polyamide resin.
[0074] The ether compounds of the present invention may include ether compounds (C-1) with an OH value of 35 mg KOH / g to 40 mg KOH / g and ether compounds (C-2) with an OH value of 1190 mg KOH / g to 1320 mg KOH / g.
[0075] For example, an ether compound (C-1) with an OH value of 35 mg KOH / g to 40 mg KOH / g and an ether compound (C-2) with an OH value of 1190 mg KOH / g to 1320 mg KOH / g can be included in a weight ratio of 1:0.5 to 1:3, preferably 1:0.7 to 1:2.5, and more preferably 1:1 to 1:2 (C-1:C-2). In this case, mechanical properties such as tensile strength and impact strength, as well as heat resistance, can be excellent.
[0076] (C-1) Ether compounds
[0077] It may contain ether compounds with an OH value of 35 mg KOH / g to 40 mg KOH / g to impart improved surface appearance and the aforementioned thermal stability.
[0078] OH value can be measured using standard methods such as ASTM D4274, ASTM D1899, ASTM D1957 and ASTM D6321.
[0079] When the ether compound has hydroxyl groups exceeding 40 mg KOH / g, it cannot sufficiently penetrate to the surface, thus failing to improve minor whitening. Therefore, the hydroxyl groups can be, for example, below 40 mg KOH / g, with a specific example being in the range of 35 mg KOH / g to 40 mg KOH / g. In this case, the thermal bonding strength between the components constituting the polyamide resin composition can be improved.
[0080] Based on a total of 100% by weight of the polyamide resin composition, the ether compound may be included in an amount preferably from 0.5% to 10% by weight, more preferably from 0.4% to 2.44% by weight, even more preferably from 0.5% to 2.4% by weight, and still more preferably from 0.8% to 2.2% by weight. In this case, kneading and molding can be easily achieved with only a small amount of addition. Furthermore, tensile strength, flexural modulus, and heat resistance can be significantly improved without deteriorating the original mechanical properties of the polyamide resin.
[0081] For example, ether compounds with an OH value of 35 mg KOH / g to 40 mg KOH / g can be poly(tetramethylene ether) glycol.
[0082] Within the scope defined by this invention, ether compounds with an OH value of 35 mg KOH / g to 40 mg KOH / g can be prepared by methods commonly used in the technical field to which this invention pertains, or commercially available products can be used, without particular limitation. For example, PTMG3000, PTMG2000, etc., can be used.
[0083] (C-2) Ether compounds
[0084] It may contain an ether compound with an OH value of 1190 mg KOH / g to 1320 mg KOH / g, to impart heat resistance and improved surface appearance to the polyamide resin composition together with the aforementioned ether compound (C-1). In this case, the thermal bonding strength between the components constituting the polyamide resin composition can be sufficiently improved.
[0085] Based on a total of 100% by weight of polyamide resin composition, an ether compound with an OH value of 1190 mg KOH / g to 1320 mg KOH / g may be included in an amount preferably from 0.1% to 10% by weight, more preferably from 0.1% to 5% by weight, even more preferably from 1% to 5% by weight, and still more preferably from 1% to 3% by weight. In this case, kneading and molding can be easily achieved with only a small amount of addition. Furthermore, tensile strength, flexural modulus, and heat resistance can be significantly improved without deteriorating the original mechanical properties of the polyamide resin.
[0086] Within the scope defined by this invention, ether compounds with an OH value of 1190 mg KOH / g to 1320 mg KOH / g can be prepared by methods commonly used in the technical field to which this invention pertains, or commercially available products can be used, without particular limitation.
[0087] For example, ether compounds with an OH value of 1190 mg KOH / g to 1320 mg KOH / g can be dipentaerythritol.
[0088] (D) Additives
[0089] The additives of this invention may include one or more selected from lubricants, antioxidants, heat stabilizers, and light stabilizers. In this case, the desired properties can be effectively achieved without degrading the original properties of the polyamide resin composition of this invention.
[0090] For example, the lubricant may include one or more selected from alkyl acrylate polymers, styrene-acrylonitrile copolymers with a weight-average molecular weight of 30,000 g / mol to 70,000 g / mol, ethylene copolymers, olefin waxes, and aliphatic amide compounds, preferably selected from alkyl acrylate polymers, styrene-acrylonitrile copolymers with a weight-average molecular weight of 30,000 g / mol to 70,000 g / mol, and olefin waxes, more preferably alkyl acrylate polymers. In this case, the appearance quality can be excellent due to the excellent balance of physical properties and scratch resistance.
[0091] For example, based on a total of 100% by weight of polyamide resin composition, a lubricant may be included in an amount of less than 5% by weight, preferably from 0.1% by weight to 5% by weight. Within this range, both releaseability and flowability can be excellent.
[0092] The alkyl acrylate polymer may preferably include one or more selected from poly(methyl acrylate), poly(ethyl acrylate), and poly(butyl acrylate). In this case, the formation of mold deposits can be suppressed, resulting in an attractive appearance and high gloss of the molded article.
[0093] As an alkyl acrylate polymer, the alkyl acrylate polymer as defined in this invention can be prepared directly, or commercially available products can be used, without particular restrictions.
[0094] Styrene-acrylonitrile copolymers with a weight-average molecular weight of 30,000 g / mol to 70,000 g / mol can preferably have a weight-average molecular weight of 40,000 g / mol to 67,000 g / mol, more preferably 50,000 g / mol to 65,000 g / mol, and even more preferably 55,000 g / mol to 65,000 g / mol. Within this range, flowability can be improved, processing performance can be excellent, and appearance quality can be improved.
[0095] For example, styrene-acrylonitrile copolymers with a weight-average molecular weight of 30,000 g / mol to 70,000 g / mol can have a melt flow index (190°C, 5 kg) of 20 g / 10 min to 60 g / 10 min, preferably 25 g / 10 min to 55 g / 10 min, as measured according to ISO 1133. Within this range, impact strength, flowability, and appearance quality can be excellent.
[0096] For example, styrene-acrylonitrile copolymers with a weight-average molecular weight of 30,000 g / mol to 70,000 g / mol can have a heat distortion temperature of 82°C to 90°C, preferably 84°C to 88°C, as measured according to ASTM D648. Within this range, impact strength, flowability, and appearance quality can be excellent.
[0097] For example, ethylene copolymers may include one or more selected from ethylene / 1-butene copolymers and ethylene / n-butyl acrylate / carbon monoxide terpolymers. In this case, heat resistance, flowability, and appearance quality can be excellent.
[0098] For example, olefin waxes may include one or more selected from polyethylene waxes and polypropylene waxes, preferably polyethylene waxes. In this case, heat resistance, flowability, and appearance quality can be excellent.
[0099] For example, aliphatic amide compounds may include one or more selected from stearamide, behenamide, ethylene bis(stearamide), N,N′-ethylene bis(12-hydroxystearamide), erucamide, oleamide, and ethylene bisoleamide, preferably ethylene bis(stearamide). In this case, impact strength, flowability, and appearance quality can be excellent.
[0100] For example, antioxidants may include one or more selected from copper and potassium compounds. In this case, heat resistance retention and resistance to discoloration can be excellent.
[0101] For example, copper compounds may include CuI, and potassium compounds may include one or more selected from KI and KBr.
[0102] For example, based on a total of 100% by weight of polyamide resin composition, an antioxidant may be included in an amount of less than 5% by weight, preferably from 0.1% by weight to 5% by weight. Within this range, the retention of physical properties can be improved by reducing the thermal history of the polymer material during thermoforming processes such as extrusion and injection molding, and the resistance to discoloration can be excellent.
[0103] For example, the heat stabilizer may include one or more selected from phenolic heat stabilizers, phosphite heat stabilizers and thioether heat stabilizers, preferably phenolic heat stabilizers or phosphite heat stabilizers.
[0104] For example, based on a total of 100% by weight of polyamide resin composition, a heat stabilizer may be included in an amount of 0.1% to 2.5% by weight, preferably 0.3% to 1.5% by weight, more preferably 0.3% to 1% by weight. In this case, heat resistance can be improved.
[0105] For example, phenolic heat stabilizers may include one or more selected from tetrakis methylene 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionatemethane, 1,3,5-tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl)-1,3,5-triazine-2,4,6-(1H,3H,5H)-trione and 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)triazine-2,4,6-(1H,3H,5H)-trione.
[0106] For example, phosphite heat stabilizers can be trinonylphenyl phosphite, tris(2,4-di-tert-butylphenyl) phosphite, bis(2,4-di-tert-butylphenyl) pentaerythritol diphosphite, or mixtures thereof.
[0107] For example, a thioether heat stabilizer may include one or more selected from dilauryl thiodipropionate, dimyristyl thiodipropionate, octadecyl dodecyl thiodipropionate, distearate thiodipropionate, dimethyl thiodipropionate, 2-mercaptobenzimidazole, phenothiazine, octadecyl mercaptoacetate, butyl mercaptoacetate, octyl mercaptoacetate, and thiocresol.
[0108] For example, based on a total of 100% by weight of polyamide resin composition, a light stabilizer may be included in an amount of 0.1% to 2.5% by weight, preferably 0.3% to 1.5% by weight, more preferably 0.3% to 1% by weight. In this case, weather resistance can be improved.
[0109] For example, the light stabilizer can be a hindered amine light stabilizer (HALS), preferably comprising a selection from 1,1-bis(2,2,6,6-tetramethyl-4-piperidinyl)succinate, bis(2,2,6,6-tetramethyl-4-piperidinyl)sebacate, bis(1,2,2,6,6-pentamethyl-4-piperidinyl)sebacate, bis(1-octoxy-2,2,6,6-tetramethyl-4-piperidinyl)sebacate, bis(1,2,2,6,6-pentamethyl-4-piperidinyl)-N-butyl-3,5-di-tert-butyl-4-hydroxybibenzoyl malonate, condensation product of 1-(2-hydroxyethyl)-2,2,6,6-tetramethyl-4-hydroxypiperidine and succinic acid, N,N′-bis(2, Linear or cyclic condensation products of 2,6,6-tetramethyl-4-piperidinyl)hexamethylenediamine and 4-tert-octylamino-2,6-dichloro-1,3,5-triazine, tris(2,2,6,6-tetramethyl-4-piperidinyl)aminotriacetate, tetra(2,2,6,6-tetramethyl-4-piperidinyl)-1,2,3,4-butanetetracarboxylate, 1,1′-(1,2-ethanediyl)-bis(3,3,5,5-tetramethylpiperazinone), 4-benzoyl-2,2,6,6-tetramethylpiperidine, 4-stearoyloxy-2,2,6,6-tetramethylpiperidine, N,N′-bis(2,2,6,6-tetramethyl-4-piperidinyl)hexamethylenediamine and 4-morpholino-2,6-di Linear or cyclic condensation products of chloro-1,3,5-triazine, reaction products of 7,7,9,9-tetramethyl-2-cycloundecyl-1-oxa-3,8-diaza-4-oxospiro-[4,5]decane with epichlorohydrin, and one or more of poly[6-(1,1,3,3-tetramethylbutyl)amino]-1,3,5-triazine-2,4-diyl][(2,2,6,6-tetramethyl-4-piperidinyl)imino]-1,6-hexadiyl[(2,2,6,6-tetramethyl-4-piperidinyl)imino], more preferably bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, 2-(2H-benzotriazol-2-yl)-4-(1,1,3,3-tetramethylbutyl) The mixture contains bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, poly[[6-(1,1,3,3-tetramethylbutyl)amino]-1,3,5-triazine-2,4-diyl][(2,2,6,6-tetramethyl-4-piperidinyl)imino]-1,6-hexanediol[(2,2,6,6-tetramethyl-4-piperidinyl)imino], or mixtures thereof, and more preferably bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, poly[[6-(1,1,3,3-tetramethylbutyl)amino]-1,3,5-triazine-2,4-diyl][(2,2,6,6-tetramethyl-4-piperidinyl)imino]-1,6-hexanediol[(2,2,6,6-tetramethyl-4-piperidinyl)imino], or mixtures thereof. In this case, weather resistance can be significantly improved without deteriorating impact strength and flowability.
[0110] When heat stabilizers and light stabilizers are included, the heat resistance can be further improved through the synergistic effect of their combination.
[0111] When necessary, based on a total of 100% by weight of the polyamide resin composition, the thermoplastic resin composition may further comprise 0.1% to 2.5% by weight, preferably 0.3% to 1.5% by weight, more preferably 0.3% to 1% by weight, of one or more selected from flame retardants, hydrolytic stabilizers, dyes, pigments, colorants, antistatic agents, crosslinking agents, antimicrobial agents, processing aids, and carbon black masterbatches. Within this range, the desired properties can be effectively achieved without degrading the inherent properties of the thermoplastic resin composition of the present invention.
[0112] Polyamide resin composition
[0113] When ISO bending specimens manufactured at temperatures between 280°C and 310°C are aged for 4 weeks at high temperature and humidity of 70°C and 62%RH and whitening is observed on the surface of the specimens, the polyamide resin composition of the present invention exhibits non-whitening characteristics.
[0114] Here, whitening refers to the phenomenon that occurs on the surface of a product when it is exposed to a high temperature and humidity environment of 70°C and 62% RH for an extended period, resulting in white spots observed on the surface. According to the present invention, no whitening phenomenon is observed, the balance of physical properties can be excellent, the heat resistance can be excellent, and the surface quality and expected lifespan can be improved.
[0115] For example, the polyamide resin composition can have a tensile strength of 170 MPa or more, more preferably 180 MPa or more, and even more preferably 190 MPa to 220 MPa, measured according to ISO 527 at a marking distance of 50 mm, a test speed of 5.0 mm / min, and at 23°C. Within this range, a balance of physical properties, heat resistance, rigidity, and impact resistance can be excellent.
[0116] For example, the polyamide resin composition can have a flexural modulus of 8,000 MPa or more, more preferably 8,500 MPa or more, and even more preferably 8,900 MPa to 9,500 MPa, as measured according to ISO 178 at a span of 64 mm and a test speed of 2.0 mm / min. Within this range, a good balance of physical properties, heat resistance, rigidity, and impact resistance can be achieved.
[0117] Method for preparing polyamide resin compositions
[0118] For example, the method for preparing the polyamide resin composition of the present invention includes the steps of kneading and extruding polyamide resin (A), glass fiber (B) and ether compound (C), wherein the ether compound (C) includes ether compound (C-1) with an OH value of 35 mg KOH / g to 40 mg KOH / g and ether compound (C-2) with an OH value of 1190 mg KOH / g to 1320 mg KOH / g.
[0119] As another example, the method for preparing the polyamide resin composition of the present invention includes the steps of kneading and extruding 39% to 89.4% polyamide resin, 4.4% to 40% glass fiber (B), 0.5% to 10% ether compound with an OH value of 35 mg KOH / g to 40 mg KOH / g (C-1), 0.1% to 10% ether compound with an OH value of 1190 mg KOH / g to 1320 mg KOH / g (C-2), and less than 5% additives (D).
[0120] For example, kneading and extrusion can be carried out using a single-screw extruder, a twin-screw extruder, or a Banbury mixer. In this case, the composition can be uniformly dispersed, thus achieving excellent compatibility.
[0121] For example, kneading and extrusion can be carried out at a barrel temperature of 200°C to 300°C, preferably 210°C to 290°C, and more preferably 210°C to 280°C. In this case, the output per unit time can be increased, and melt kneading can be fully achieved. In addition, thermal decomposition of the resin components can be prevented.
[0122] For example, kneading and extrusion can be performed at screw speeds of 200 rpm to 300 rpm, preferably 220 rpm to 280 rpm, and more preferably 230 rpm to 270 rpm. Within this range, the output per unit time can be increased, and process efficiency can be improved. Furthermore, over-cutting can be prevented.
[0123] The polyamide resin composition obtained by kneading and extrusion can preferably be provided in granular form.
[0124] There are no particular restrictions on the type of extruder, and extruders commonly used in the field can be appropriately selected and used. For example, a single-screw extruder equipped with one screw or a multi-screw extruder equipped with multiple screws can be used. Considering the uniform kneading of materials, ease of processing, and economic efficiency, a twin-screw extruder equipped with two screws is preferred.
[0125] An extruder includes a feeder for supplying material into the barrel, a screw for conveying and kneading the supplied material, and a die for extruding the kneaded material. In this case, the screw consists of multiple screw elements for various functions.
[0126] One or more feeders may be provided. Optionally, two or more feeders may be provided. For example, a main feeder and optional auxiliary feeders may be provided. Optionally, more than two auxiliary feeders may be provided.
[0127] The kneading block of the present invention corresponds to a screw element. Specifically, each kneading block consists of a plurality of discs, preferably 3 to 7 discs, 5 to 7 discs, 3 to 5 discs, or 4 to 5 discs, and has a polygonal or elliptical cross-section. The kneading blocks are arranged continuously in the direction of material conveying. Furthermore, in the kneading block, the phase angle (referring to the travel angle between discs) of the discs is preferably 45° to 90°.
[0128] In addition, kneading blocks include forward kneading blocks capable of conveying, dispensing and mixing materials, neutral kneading blocks capable of dispensing and mixing materials without conveying materials, and reverse kneading blocks capable of conveying materials in the opposite direction to the conveying direction.
[0129] Molded products
[0130] For example, the molded articles of the present invention comprise the polyamide resin composition of the present invention. In this case, the heat resistance may be superior to that of conventional polyamide resin compositions.
[0131] A method for manufacturing a molded article includes an injection molding step of producing an extruded product by means of preparing a polyamide resin composition. In this case, a molded article having rigidity, impact resistance, and heat resistance can be readily manufactured.
[0132] During injection, the injection temperature (cylinder temperature) is preferably between 250°C and 300°C, more preferably between 260°C and 290°C. Within this range, injection-molded products requiring complex designs can be easily manufactured.
[0133] During injection, the pressure can preferably be from 20 bar to 90 bar, more preferably from 40 bar to 80 bar. Within this range, injection-molded products requiring complex designs can be easily manufactured.
[0134] During injection, the holding pressure is preferably between 20 bar and 80 bar, more preferably between 30 bar and 60 bar. Within this range, injection-molded products requiring complex designs can be easily manufactured.
[0135] Molded products can be those that require rigidity, impact resistance, and heat resistance.
[0136] Molded parts can be automotive parts or electrical and electronic components.
[0137] For example, the molded articles can be automotive hoods, lower covers, intercoolers, AIMs, and manifolds. In such cases, by using the thermoplastic resin composition of the present invention, a high quality exceeding market requirements can be provided.
[0138] In describing the polyamide resin compositions of the present invention, the methods for preparing the polyamide resin compositions, and the molded articles, it should be noted that other conditions or equipment not explicitly described herein may be suitably selected within the scope of ordinary practice in the art, without particular limitation.
[0139] The invention will now be described in more detail with reference to the preferred embodiments described below. However, these embodiments are provided for illustrative purposes only and should not be construed as limiting the scope and concept of the invention. Furthermore, it will be apparent to those skilled in the art that various changes and modifications can be made without departing from the concept and scope of the invention, and such changes and modifications are also within the scope of the appended claims.
[0140] [Example]
[0141] The components used in the following examples and comparative examples are as follows.
[0142] *A1) Polyamide: (Amorphous: 50% to 60% by weight, Melting point (Tm): 259°C to 261°C, Relative viscosity (RV): 2.4)
[0143] *A2) Polyamide (amorphous: 50% to 60% by weight, melting point (Tm): 220°C, relative viscosity (RV): 2.5)
[0144] *(B) Glass Fiber: High-strength, non-circular, flat glass fiber comprising 52% to 56% silica; 12% to 16% alumina; 21% to 25% calcium oxide and magnesium oxide (magnesium oxide: less than 1.5% by weight); less than 1% titanium dioxide; 5% to 8% boron oxide; and less than 2.0% by weight of the remainder including sodium oxide, potassium oxide, and iron oxide, having a tensile modulus of 83 GPa to 87 GPa as measured by ASTM D2343 for 17 μm, 2400 tex rovings, and an aspect ratio of 1:4 (L / D, D: 7 μm).
[0145] *(C-1) Ether compounds: PTMG3000 with a hydroxyl group of 37 mg KOH / g
[0146] *(C-2) Ether compounds: Dipentaerythritol (DPE) with an OH value of 1190 mg KOH / g to 1320 mg KOH / g.
[0147] *(D) Additives
[0148] Additive 1: Lubricant (Clariant Co., product name: LICOWAX-OP)
[0149] Additive 2: Antioxidant (Product Name: KI, CuI)
[0150] Examples 1 and 2, and Comparative Examples 1 to 5
[0151] According to the contents shown in Table 1, the components shown in Table 1 were fed into a twin-screw extruder (SM Co., T40) and melt-kneaded and extruded at a temperature of 250°C and a rotational speed of 250 rpm at a flow rate of 60 kg / h to obtain granules. Using these granules, test specimens were manufactured using an injection molding machine (Engel, 80 tons).
[0152] The twin-screw extruder has two or more inlets, and all components are fed into the main inlet. Additive 1 and Additive 2 are added at 0.3 wt% and 0.3 wt% respectively, for a total of 0.6 wt%.
[0153] [Experimental Example]
[0154] The performance of the samples manufactured in Examples 1 and 2, and Comparative Examples 1 to 5, was measured using the following methods, and the results are shown in Table 1 below.
[0155] Specific gravity (g / cm³) 3 ): Measured according to ISO 1183.
[0156] *Tensile strength (MPa): Measured according to ISO 527 at a marking distance of 50 mm, a test speed of 5.0 mm / min, and a temperature of 23 °C.
[0157] * Flexural modulus (MPa): Measured according to ISO 178 at a span of 64 mm and a test speed of 2.0 mm / min.
[0158] *Heat resistance tensile strength retention rate (%): The tensile strength of the specimens before and after aging at 200°C for 1000 hours is measured according to ISO 527, and the heat resistance tensile strength retention rate is calculated using Equation 1 below.
[0159] [Equation 1]
[0160] Heat resistance tensile strength retention rate (%) = [Tensile strength after aging / Tensile strength before aging] × 100
[0161] *Color L value: The color L value of the specimen was measured according to ISO 7724 / 1 after aging at 70°C and 62%RH for 4 weeks.
[0162] [Table 1]
[0163]
[0164]
[0165] As shown in Table 1, in the case of the polyamide resin composition according to the present invention (Examples 1 and 2), the evaluation items of tensile strength, flexural modulus, heat resistance tensile strength retention rate and thermal stability of the specimens are superior compared with the polyamide resin compositions outside the scope of the present invention (Comparative Examples 1 to 5).
[0166] On the other hand, in Comparative Example 1, which did not use the ether compound (C-1), the appearance of the sample was poor compared to Example 1 due to its poor thermal stability.
[0167] In addition, in Comparative Example 2, which used a small amount of ether compound (C-1), the appearance of the sample was significantly worse than that of Example 1 due to the deterioration of heat resistance, tensile strength retention and thermal stability.
[0168] In addition, in Comparative Example 3, which used an excessive amount of ether compound (C-1), the appearance of the specimens was significantly worse than that of Example 1 in terms of flexural modulus, heat resistance tensile strength retention rate, and thermal stability.
[0169] In addition, in Comparative Example 4, which used a small amount of ether compound (C-2), the appearance of the sample was significantly worse than that of Example 1 in terms of tensile strength, heat resistance tensile strength retention rate, and thermal stability.
[0170] In addition, in Comparative Example 5, where an excessive amount of ether compound (C-2) was used, the specific gravity and tensile strength of the sample were significantly lower than those of Example 1.
[0171] In summary, when a polyamide resin composition is prepared by mixing polyamide resin, glass fiber, and an ether compound satisfying a specific OH value in a predetermined compositional ratio, the molded articles comprising this polyamide resin composition exhibit excellent tensile strength, flexural modulus, and heat resistance, and are virtually unaffected by heat caused by exposure to the external environment. Therefore, the molded articles can be used in automotive or electrical / electronic components.
Claims
1. A polyamide resin composition comprising: a polyamide resin (A), glass fibers (B), and an ether compound (C), wherein the ether compound (C) includes an ether compound (C-1) having an OH value of 35 mgKOH / g to 40 mgKOH / g and an ether compound (C-2) having an OH value of 1190 mgKOH / g to 1320 mgKOH / g. 2.A polyamide resin composition comprising: 39 wt% to 89.4 wt% of a polyamide resin (A), 4.4 wt% to 40 wt% of glass fibers (B), 0.5 wt% to 10 wt% of an ether compound (C-1) having an OH value of 35 mgKOH / g to 40 mgKOH / g, 0.1 wt% to 10 wt% of an ether compound (C-2) having an OH value of 1190 mgKOH / g to 1320 mgKOH / g, and 5 wt% or less of an additive (D).
3. The polyamide resin composition according to claim 1 or 2, wherein, the ether compound (C-1) has a number average molecular weight of 2600 g / mol to 3200 g / mol, and the ether compound (C-2) has a number average molecular weight of 100 g / mol to 400 g / mol.
4. The polyamide resin composition according to claim 1 or 2, wherein, the ether compound (C-1) and the ether compound (C-2) are included in a weight ratio (C-1:C-2) of 1:0.5 to 1:
5.
5. The polyamide resin composition according to claim 1 or 2, wherein, the glass fibers include: 52 wt% to 56 wt% of silica; 12 wt% to 16 wt% of alumina; 21 wt% to 25 wt% of calcium oxide and magnesium oxide (magnesium oxide: 1.5 wt% or less); 1 wt% or less of titanium dioxide; 5 wt% to 8 wt% of boron oxide; and less than 2.0 wt% of a remainder including sodium oxide, potassium oxide, and iron oxide.
6. The polyamide resin composition according to claim 2, wherein, the additive includes one or more selected from a lubricant, an antioxidant, a heat stabilizer, and a light stabilizer.
7. The polyamide resin composition according to claim 1 or 2, wherein, the polyamide resin composition has a tensile strength of 170 MPa or more measured according to ISO 527 at a mark distance of 50 mm, a test speed of 5.0 mm / min, and a temperature of 23℃, and a flexural modulus of 8800 MPa or more measured according to ISO 178 at a span of 64 mm and a test speed of 2.0 mm / min. 8.A method of preparing a polyamide resin composition, comprising kneading and extruding a polyamide resin (A), glass fibers (B), and an ether compound (C), wherein the ether compound (C) includes an ether compound (C-1) having an OH value of 35 mgKOH / g to 40 mgKOH / g and an ether compound (C-2) having an OH value of 1190 mgKOH / g to 1320 mgKOH / g.
9. A method for producing a polyamide resin composition, comprising kneading and extruding 39 to 89.4% by weight of a polyamide resin (A), 4.4 to 40% by weight of glass fibers (B), 0.5 to 10% by weight of an ether compound (C-1) having an OH value of 35 to 40 mgKOH / g, 0.1 to 10% by weight of an ether compound (C-2) having an OH value of 1190 to 1320 mgKOH / g, and 0 to 5% by weight of an additive (D).
10. A molded article comprising the polyamide resin composition according to claim 1.
11. The molded article of claim 10, wherein, The molded article is an automobile part or an electrical and electronic part.
Citation Information
Patent Citations
Polyamide resin composition
JP2014148560A
Attachment with 3pinhole structue
KR1020240058654A